KONTRIBUSI BRICS PARTNERSHIP ON NEW INDUSTRIAL REVOLUTION (PartNIR) TERHADAP EKONOMI DIGITAL BERBASIS KECERDASAN BUATAN DI TIONGKOK TAHUN 2019-2025 - Muhammad Ikhsan; Arif Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The transformation of China’s AI driven digital economy faces structural constraints in the form of a fragmented digital ecosystem, largely shaped by the dominance of walled garden strategies employed by major technology companies such as Baidu, Alibaba, and Tencent. This fragmentation limits cross-sectoral data interoperability and is further exacerbated by global geopolitical pressures and dependence on Western technological infrastructure. In response, China leverages the BRICS Partnership on New Industrial Revolution (PartNIR) as a strategic instrument to enhance domestic efficiency and strengthen technological sovereignty. The findings indicate that BRICS PartNIR serves as a platform of legitimacy for the norm of AI sovereignty, supporting the implementation of China’s national AI policies. Standardization within this regime acts as a forcing mechanism that encourages domestic technology firms to adopt more open systems in order to enhance intra-BRICS market integration. Keywords: BRICS PartNIR, Digital Economy, Artificial Intelligence (AI), China, International Regime, Digital Sovereignty, Interoperability